Mortality through associated illnesses in tuberculosis patients and post-mortem pulmonary tuberculosis diagnosis in Chisinau - Vasile Popa (The Moldovan Medical Journal, 2017)
Background: The main cause of death of tuberculosis patients is the progression of tuberculosis, but the presence of associated diseases decreases the outcome of treatment of both the underlying and the associated disease, and the latter is the cause of death. Thus, reducing the mortality of tuberculosis patients can be solved by increasing the therapeutic success rate of tuberculosis as well as associated diseases. Material and methods: A selective, descriptive and retrospective study was carried out in 3 time periods: period I (2001-2003) – implementation of the DOTS strategy in Chisinau municipality; period II (2007-2009) characterized by the tense epidemiological situation, the high TB mortality indicator and the implementation of the STOP TB strategy; period III (2013-2015) characterized by a shift to “End TB” strategy and a marked decrease in tuberculosis mortality. Results: Analyzing the reference periods, we found that in the 1st period 1/4 of the total deaths were caused by tuberculosis, associated diseases and other causes, in the 2nd period there was a decrease in the number of deaths, and in the 3rd period there was about 2 times increase in the number of deaths. Conclusions: The most common concomitant diseases were: oncological, cardiovascular, hepatic cirrhosis and other causes. The number of deaths with the post-mortem tuberculosis diagnosis was decreasing; half of them occurred at home, ½ of the deceased were without a stable place of living.